Invitation to oceanography - Pinet, Paul R. (Jones & Barllett learning, 2016)
Each new print copy includes Navigate 2 Advantage Access that unlocks a comprehensive and interactive eBook, student practice activities and assessments, a full suite of instructor resources, and learning analytics reporting tools.